Business value assessment of services re-use on SOA using appropriate methodologies, metrics and models. (1st January 2013) - Kryvinska, Natalia; Baroková, Alexandra; Auer, Lukas; Ivanochko, Iryna; Strauss, Christine
The main advantage of service re-use for the companies includes retaining a competitive advantage. The expectation of greater service re-use is one of the core benefits of a service-oriented architecture (SOA). Besides the top drivers for SOA adoption include business flexibility, simplification and speed of integration. So, in order to maximise the intended benefits of SOA implementation, organisations need to develop a well-articulated SOA quality strategy to promote trust and re-use. However, the shift to this strategy does not come easy and cheap. Building an effective SOA platform requires tight integration between new and existing product categories, and it may require large investments. The same applies for developing re-usable services. For this reason, conventional investment valuation methods need to be combined with other modern techniques to reflect service re-use's long-term strategic investment nature, the inherent uncertainty and the managerial discretion. Many value-based analytical methodologies have started to be developed. Thus, in this paper, we explain the role of SOA for services re-use and focus on the methodologies, metrics and models that are able to measure the business value of service re-use.